2004
DOI: 10.1042/bj20030708
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stat3 (signal transducer and activator of transcription 3) dimerization by fluorescence resonance energy transfer in living cells

Abstract: Signal transducer and activator of transcription 3 (Stat3) dimerization is commonly thought to be triggered by its tyrosine phosphorylation in response to interleukin-6 (IL-6) or other cytokines. Accumulating evidence from in vitro studies, however, suggests that cytoplasmic Stat3 may be associated with high-molecular-mass protein complexes and/or dimerize prior to its activation. To directly study Stat3 dimerization and subcellular localization upon cytokine stimulation, we used live-cell fluorescence spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 36 publications
9
89
0
3
Order By: Relevance
“…Yet, in high-grade gliomas of both human and mouse tumours, we observed, in addition to the expected nuclear localization, a novel distinct plasma membrane-associated immunoreactivity for pY-STAT3. This observation is compatible with recent findings, suggesting that STAT proteins do not float solely as free monomers in the cytosol of mammalian cells but constitute high molecular mass protein complexes in lipid rafts (Sehgal et al, 2002) and/or dimerize prior to its activation (Kretzschmar et al, 2003). Raft proteins reside in specialized microdomains at the cell surface and are thought to play an important role in receptor signalling.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Yet, in high-grade gliomas of both human and mouse tumours, we observed, in addition to the expected nuclear localization, a novel distinct plasma membrane-associated immunoreactivity for pY-STAT3. This observation is compatible with recent findings, suggesting that STAT proteins do not float solely as free monomers in the cytosol of mammalian cells but constitute high molecular mass protein complexes in lipid rafts (Sehgal et al, 2002) and/or dimerize prior to its activation (Kretzschmar et al, 2003). Raft proteins reside in specialized microdomains at the cell surface and are thought to play an important role in receptor signalling.…”
Section: Discussionsupporting
confidence: 92%
“…Live cell imaging (FRET) demonstrated that fusion proteins with spectral variants of green fluorescent protein, CFP and YFP redistributed -like wildtype STAT3 -from a preferentially cytoplasmic to a nuclear localization upon IL-6 stimulation. Normalizing FRETc/YFP signals revealed a gradient from the plasma membrane to the cell interior demonstrating a steady state of STAT3 activation at the plasma membrane and inactivation in the nucleus (Kretzschmar et al, 2003). Thus, the plasma membrane-associated immunoreactivity of pY-STAT3 seen in our gliomas in all likelihood resembles an acute signalling state of a stimulated cell.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Remarkably, the maximum FRET signal for interacting partners increased 14-fold over that obtained with noninteracting partners (Fig. 2B), a dynamic range substantially greater than that observed by using nonoptimized fluorescent protein FRET pairs to detect protein interactions (25)(26)(27). These results demonstrated that the YPetMona/CyPet-P2 interaction could be specifically detected by using FRET hybrids in complex cell lysates when using FREToptimized probes CyPet and YPet.…”
Section: Analysis Of Known Interaction Partners By Using Fret Hybridsmentioning
confidence: 72%
“…Transcription factors have to enter the nucleus to exhibit their function. Accordingly, fusion proteins of transcription factors such as NFB subunits or STATs have been used to monitor nuclear entry (Birbach et al, 2004;Kretzschmar et al, 2004;Pranada et al, 2004). Another obvious group of proteins are those involved in nuclear import and export (Plafker and Macara, 2002).…”
Section: Translocation As Readoutmentioning
confidence: 99%